2001
DOI: 10.4049/jimmunol.167.9.5129
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Mutants of High-Affinity and Low-Affinityp-Azophenylarsonate-Specific Antibodies Generated by Alanine Scanning of Heavy Chain Complementarity-Determining Region 2

Abstract: Alanine scanning was used to determine the affinity contributions of 10 side chain amino acids (residues at position 50–60 inclusive) of H chain complementarity-determining region 2 (HCDR2) of the somatically mutated high-affinity anti-p-azophenylarsonate Ab, 36–71. Each mutated H chain gene was expressed in the context of mutated (36–71L) and the unmutated (36–65L) L chains to also assess the contribution of L chain mutations to affinity. Combined data from fluorescence quenching, direct binding, inhibition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Homologue scanning, an alternative method that involves replacement of wild-type residues with amino acids having similar side-chain chemistries, is thought to further define a subset of paratope residues that are an absolute requirement for antigen binding (9). In the majority of cases, it has been concluded that residues within the functional paratope should not be randomized for improved potency, because they are likely to be intolerant of any amino acid substitutions (11,12). Alanine and homologue scanning are therefore reliable methods to determine which residues to avoid mutating during the process of antibody optimization.…”
mentioning
confidence: 99%
“…Homologue scanning, an alternative method that involves replacement of wild-type residues with amino acids having similar side-chain chemistries, is thought to further define a subset of paratope residues that are an absolute requirement for antigen binding (9). In the majority of cases, it has been concluded that residues within the functional paratope should not be randomized for improved potency, because they are likely to be intolerant of any amino acid substitutions (11,12). Alanine and homologue scanning are therefore reliable methods to determine which residues to avoid mutating during the process of antibody optimization.…”
mentioning
confidence: 99%
“…A register-shift error in the complementarity determining region (CDR) L2 residues L51–L57 was also corrected. This register shift is not found in the search model (1jfq; Fab 36–71 with anti- p -azophenylarsonate; [68]) used for molecular replacement. However, this error could easily be propagated into any structures using 2a6i as a molecular replacement probe.…”
Section: Lack Of Evidence Implausible Geometry and Abundant Collisiomentioning
confidence: 99%